2019
DOI: 10.1177/016146811912100406
|View full text |Cite
|
Sign up to set email alerts
|

How Do 2-Year College Students Beginning in STEM View Themselves as Learners?

Abstract: Background Two-year colleges are uniquely positioned to diversify science, technology, engineering, and mathematics (STEM) education. Yet limited existing scholarship sheds light on how 2-year college students view themselves as learners as they experience STEM courses and programs. An in-depth and nuanced understanding of 2-year college STEM students’ self-perceptions as learners presents a powerful vehicle for identifying venues of interventions aimed at cultivating and supporting the STEM talent pool toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Some studies have indicated that the college years represents a peak period of social anxiety, and approximately 80% of social anxiety occurs before the age of 20 [3]. A report entitled "Social Phobia in China," was published by the South China Morning Post on April 5, 2022. According to the report, approximately 32% of individuals' aged of 16 and 29 in China met the medical criteria for social phobia.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that the college years represents a peak period of social anxiety, and approximately 80% of social anxiety occurs before the age of 20 [3]. A report entitled "Social Phobia in China," was published by the South China Morning Post on April 5, 2022. According to the report, approximately 32% of individuals' aged of 16 and 29 in China met the medical criteria for social phobia.…”
Section: Introductionmentioning
confidence: 99%
“…This study finds themes such as Support and Motivation to be prevalent in student responses. These themes are backed by Wang , Sun, Wagner, & Nachman [4] when they discuss the theme of Support with the quote: "[the students] saw self-worth when their capacity to transfer knowledge was evidenced by teaching others" and the expression of the importance of building community in an institution. The theme of Motivation is also present by stating: "other students became or remained enthused and gratified learners when seeing the applied nature of STEM subjects" [4].…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this study was to see how students' self-perceptions of themselves as learners are developed and change over time. "Our study captures how these students' self-perceptions as learners are formed and transformed and illustrates how their prior and current learning experiences, self-perceptions as mathematics learners, background characteristics, and relationships with others interweave to shape and reshape how they view themselves as learners" [4]. One of the interview questions used in this study was: "To begin, could you tell me a bit about your experiences as a student at [name of institution], since last fall?"…”
Section: Related Researchmentioning
confidence: 96%
See 1 more Smart Citation